Systemic Infection Caused by Malassezia pachydermatis in Infants: Case Series and Review of the Literature. Issue 5 (May 2020) - Huang, Ching-Ying; Peng, Chun-Chih; Hsu, Chyong-Hsin; Chang, Jui-Hsing; Chiu, Nan-Chang; Chi, Hsin
Abstract : Background: Malassezia pachydermatis is a rare cause of systemic infection in infants. Methods: A total of 4 cases of M. pachydermatis fungemia that occurred in our neonatal intensive care unit over a 21-month period were reviewed, as well as 27 cases reported in the literature since 1988. Results: The patients were preterm with multiple complications and had birth weights ranging from 490 to 810 g and gestational age between 23 and 26 weeks. All patients had received prophylactic fluconazole, broad-spectrum antibiotics and parenteral lipid supplements before fungemia onset, which occurred between the age of 7 and 28 days. Symptoms were nonspecific and thrombocytopenia was the primary laboratory finding. All patients received intravenous antifungal treatment and recovered from their infection. The 27 cases from review of the literature also indicated that the infected infants were extremely low birth weight (77.8%), with multiple underlying diseases (94.7%), receiving lipid-supplementation (100%) from a central vascular catheter. Most infants received antifungal treatment (73.1%) and catheter removal (73.1%) as the management. Conclusions: M. pachydermatis is a pathogenic agent that causes late onset sepsis in critically ill low birth weight infants with generally good outcomes. Targeted antifungal treatment as well as catheter removal appear to be key factors for infection management. Abstract : Supplemental Digital Content is available in the text.